THE ROLE OF INFORMATION TECHNOLOGY SENIOR SOCIAL ADJUSTMENT - Daugule, Anita; Dzindzuka, Sandra; Grabusts, Pēteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
Nowadays the rapid aging of the population is the world's one of the actual problems. Many governments are unable to meet the needs of seniors and thus isolating them from society. This problem is very acute in Latvia also. Seniors are too few opportunities to participate in social life. Currently, Latvian seniors are part of the population, which are excluded from the society after retiring. Summarizing positive experience of the various countries, it can be adapted to the Latvian situation to help seniors feel better in society. Nowadays, information technology is a good way for including seniors in social life.